PENGEMBANGAN MODEL THEORY OF PLANNED BEHAVIOR UNTUK ANALISIS NIAT MENGGUNAKAN TAS BELANJA RAMAH LINGKUNGAN PADA SUPERMARKET MODERN - Almuhaymin, Rizki; Jatiningrum, Wandhansari Sekar (Prodi Teknik Industri, Universitas AKPRIND Indonesia, 2022)
The use of eco-friendly shopping bags needs to be encouraged to reduce the use of plastic bags. According to the results of observations and interviews, it is known that the interest of students in using environmentally friendly shopping bags is still low. The aim of this study is to analyze the factors that influence the intention of students in using environmentally friendly shopping bags in the Special Region of Yogyakarta. This study uses multiple linear regression method. Purposive sampling is applied, with a sample of students from 5 universities as many as 100 respondents. Variables in this study using the development of Theory of Planned Behavior by adding variables of environmental awareness and support for the Prohibition of plastic bags. The results showed the correlation coefficient of 0.781 and the coefficient of determination of 0.609, which means there is a strong linear relationship between the dependent variable and all independent variables. Attitude variables, behavioral control and support for the Prohibition of plastic bags bags proved to have a significant effect on the intention to use environmentally friendly shopping bags for each value of regression coefficients were 0.221, 0.400 and 0.158, while the subjective norms and environmental awareness variables had no significant effect. For this reason, recommendations are given to variables that are proven to have a significant effect. Attitude variables are encouraged by promoting the use of environmentally friendly shopping bags to the public through various media, while for behavioral control variables, socialization needs to be carried out to the public regarding the importance of using environmentally friendly shopping bags and the adverse effects of using plastic bags. For recommendations related to variable support for the Prohibition of plastic bags can be done by encouraging plastic bag manufacturers to produce plastic bags from environmentally friendly materials (bioplastics).